Diskursus Adat dan Agama: Studi Kritis Tradisi Jujuran dalam Pernikahan Masyarakat Banjar menurut Islam - Eka Susanti; Ali Asikin Noor (Jurnal Kajian Islam dan Sosial Keagamaan, 2026)
The Jujuran tradition is one of the customary practices deeply rooted in the marriage system of the Banjar community. This tradition functions not only as a symbol of sincerity and respect toward the bride’s family but also reflects the social, economic, and cultural relations within society. However, in contemporary practice, Jujuran has often undergone a shift in meaning from an ethical customary symbol to a material demand that can be burdensome and may generate social problems, such as the postponement of marriage. This study employs a qualitative approach using library research and field studies conducted through interviews. The findings suggest that the Jujuran tradition is acceptable in Islam, provided it does not contradict Islamic law, is non-coercive, and adheres to the principles of ease and justice in marriage. Therefore, a critical and contextual reinterpretation of the Jujuran tradition is essential to ensure its alignment with Islamic values while remaining responsive to the social dynamics of contemporary Banjar society.